Zástupné a opisné pomenovania v onlinovej publicistike ako nosiče komunikačných stratégií - VLADIMÍR PATRÁŠ (Stylistyka)
In this paper, we have focused on the location of personal aliases, their placement in the media environment, and the assumed or constructed value profile of the above-mentioned names occurring in media communication interactions. A representative set of descriptive name or alias variants of personal proper names used by media-exposed actors in social and political life, which appear in journalism at the turning points or during the crisis periods, allows detecting and interpreting the identification (individualizing, differentiating) potential, ambition to reach pragmastylistic fixing (of a collocation) and its application in contemporary online opinion journalism. The material base is formed, and the space for arguments is provided by aliases and descriptive names acting in the initial texts of both online mainstream and participatory (civic, alternative) journalistic products, as well as in the related online discussion forums.